Indigenous Knowledge Systems and Curriculum Transformation: A Cross-Sectional Study of Faculty Readiness in Indonesian Higher Education - Andi Fatihah Syahrir; Desiree Montesinos; Farah Faiza (Enigma Institute, 2025)
Higher education institutions worldwide face the challenge of integrating Indigenous Knowledge Systems into curricula historically shaped by Western epistemological paradigms, yet empirical evidence on the factors influencing faculty readiness for such integration remains limited, particularly in Southeast Asian contexts. This cross-sectional mixed-methods study examined faculty attitudes, institutional resistance, and curriculum transformation readiness related to Indigenous Knowledge Systems integration among 412 faculty members at six higher education institutions in major Indonesian cities, complemented by 28 in-depth interviews. Participants completed validated instruments assessing IKS integration attitudes, curriculum transformation readiness, perceived institutional resistance, teaching self-efficacy for IKS, and student cultural competency. Significant disciplinary differences were observed across all outcomes, with Social Sciences faculty reporting the highest integration attitudes (4.12 ± 0.71) and Engineering faculty the lowest (2.87 ± 0.89; F(3, 408) = 42.67; p < 0.001). Faculty with prior IKS training demonstrated significantly higher readiness (3.89 ± 0.72 vs. 2.96 ± 0.88; p < 0.001; Cohen’s d = 1.16). Multivariate logistic regression identified prior IKS training (OR = 3.87; 95% CI: 2.48–6.04), Social Sciences discipline (OR = 3.21; 95% CI: 1.78–5.79), and low institutional resistance (OR = 2.56; 95% CI: 1.72–3.81) as the strongest independent predictors of high integration readiness. These findings highlight the critical role of faculty professional development and institutional support in advancing curriculum decolonization in Indonesian higher education.